Implementation of Learning Management with the Deep Learning Approach: A Multi-Site Study in Sidoarjo toward SDG 4 - Aris Setiawan; Yatim Riyanto; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To describe, analyze, and construct propositions regarding a conceptual model of learning management with the Deep Learning approach at State Junior High School 1 Gedangan and State Junior High School 4 Sidoarjo. Method: Using a descriptive qualitative design with a multi-site case study approach. Data were analyzed to explore the role of school principals, teachers, curriculum integration, infrastructure, digital technology, and stakeholder collaboration in supporting the implementation of Deep Learning-based learning management. Results: The findings show that school principals do not only perform managerial functions but also strengthen their role as transformational leaders. They facilitate teacher professional development through coaching, mentoring, and supportive clinical discussions. The principal’s transformational leadership becomes a determining factor in translating the curriculum vision into real action through the principles of mindful, meaningful, and joyful learning. The implementation of learning management with the Deep Learning approach requires the strengthening of human resources, especially teachers, as well as the improvement of principals’ managerial competencies, curriculum integration, optimization of facilities and digital technology, and collaboration with stakeholders. Novelty: Offering a conceptual model of learning management based on the Deep Learning approach by emphasizing the strategic role of transformational school leadership in aligning policy commitment, teacher and student mindset transformation, and managerial strategies in educational units. The proposed model contributes to SDG 4 by promoting inclusive, equitable, and quality education through meaningful, mindful, and joyful learning practices.